2019
DOI: 10.37107/jhas.36
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Practice on Reproductive Heath Rights among Married Women in Nepal

Abstract: Reproductive health rights ensure that people are able to have satisfying and safe sex life and that they have the capacity to reproduce with freedom to decide, when and how often to do so. This study aimed to assess the knowledge and practices on reproductive health rights among madhesi married women. A descriptive cross-sectional study was conducted among 384 madhesi married women of reproductive age in Sarlahi district conducted from July 2014 to December 2014. Data were entry in Epidata software and analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
1
3
2
Order By: Relevance
“…The current study showed that more than half (56.3%) of respondents decided on birth spacing by couples. The study by Y. Rajesh Kumar et al showed that 58% of both husband and wife decisions on birth spacing which is similar to this study [11].…”
Section: Discussionsupporting
confidence: 89%
“…The current study showed that more than half (56.3%) of respondents decided on birth spacing by couples. The study by Y. Rajesh Kumar et al showed that 58% of both husband and wife decisions on birth spacing which is similar to this study [11].…”
Section: Discussionsupporting
confidence: 89%
“…The difference with Ghana might be due to study design and study population, both sexes of adolescent students were involved in the study. On other hand, the level of knowledge in this study is higher than the study conducted in Sri Lanka (24.4%) ( 20 ), Nepal (37%) ( 23 ), India (9.1%) ( 26 ), Nigeria (45.2%) ( 17 ), and shire town, Northern Ethiopia (47.1%) ( 31 ). This might be because of cultural, socio-demographic profile of the study population, study area, and year of study differences.…”
Section: Discussioncontrasting
confidence: 73%
“…It is the right of an individual to decide and choose about reproduction free of discrimination, coercion, and violence ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…This was contrary to studies conducted in India [35], Bale Zone, Ethiopia [24], Arbaminch, Ethiopia [45], and Bangladesh [22] and southern Ethiopia [15]. The reason for the difference might be a disparity in the study sample and community health Nurses in India and Health Extension Workers in Ethiopia play a pivotal role in this di culty [3,14,25].…”
Section: Discussionmentioning
confidence: 66%
“…Available evidence indicated that maternal health outcomes in LIMCs are related to the inadequacy of husbands' knowledge and involvement related to reproductive rights, lack of reproductive education, and spousal discussions which are the main cause of violations in reproductive rights [22,24,25,26,27,28,29]. Likewise, major contributing factors related to male partners' involvement in partners' reproductive rights are accessibility and utilization experience of reproductive health services, lack of spousal discussions on reproductive health and transportation access, and time to reach a health institution [30,31,32].…”
Section: Introductionmentioning
confidence: 99%